Multielement Doped Barium Strontium Titanate Nanomaterials as Capacitors. (6th April 2023) - Ruthramurthy, Balachandran; Gebremedhn Kelele, Kiflom; Murthy, H. C. Ananda; Tan, Kar Ban; Chan, Kah Yoong; Muniswamy, Dhanalakshmi; Tadesse, Aschalew; Ghotekar, Suresh
Abstract : Due to the growing demand of energy and wastage of energy, there exists an interest of storing energy so that it could be utilized efficiently. Capacitors are materials designed for such an application. Ferroelectric materials are known for their application as capacitors. Of such materials, perovskites are the preferable classes of materials that have been used as capacitors. Barium strontium titanate nanomaterial is a member of perovskites which encompasses a smaller dielectric loss, elevated dielectric constant, and good thermal stability. Research studies also clarified that incorporating dopants into a barium strontium titanate nanomaterial of high dielectric materials including metal/metal oxides enhances their efficiency and effectiveness. Moreover, multielement doping or codoping has shown better dielectric properties as compared to the unidoping of BST. In this review, barium strontium titanate capacitors codoped with more than one metal/metal oxides have been studied most of which have shown that the codoped barium strontium titanate materials possess improved and sufficient dielectric properties to be utilized as capacitors. We believe that this work will have of its own contribution on understanding the doped barium strontium titanate nanomaterial by clarifying the most probable and detail reasons behind the enhancement of dielectric properties of codoped barium strontium titanate nanomaterials.